Extension of Chronological Lifespan by Hexokinase Mutation in Kluyveromyces lactis Involves Increased Level of the Mitochondrial Chaperonin Hsp60 - Lisa Rizzetto; Elena Zanni; Daniela Uccelletti; Ileana Ferrero; Paola Goffrini (Journal of Aging Research)
Oxidative damage, mitochondrial dysfunction, genomic instability, and telomere shortening represent all molecular processes proposed as causal factors in aging. Lifespan can be increased by metabolism through an influence on such processes. Glucose reduction extends chronological lifespan (CLS) of Saccharomyces cerevisiae through metabolic adaptation to respiration. To answer the question if the reduced CLS could be ascribed to glucose per se or to glucose repression of respiratory enzymes, we used the Kluyveromyces lactis yeast, where glucose repression does not affect the respiratory function. We identified the unique hexokinase, encoded by RAG5 gene, as an important player in influencing yeast lifespan by modulating mitochondrial functionality and the level of the mitochondrial chaperonin Hsp60. In this context, this hexokinase might have a regulatory role in the influence of CLS, shedding new light on the complex regulation played by hexokinases.